The effects of commercialisation on urban heritage in Tianjin: a study of citizens’ livelihood in the Five Avenues (Wudadao) historical district - Xiaochen Liu (Built Heritage)
Abstract This article examines the intersection of commercialisation and sustainable development within the context of urban heritage conservation and the related effects on citizens’ livelihoods, with a specific focus on the Five Avenues (hereafter referred to as Wudadao) historical district in Tianjin, China. The Wudadao district, which is known for its complex heritage architecture, historical significance, and multilayered socioeconomic context, offers significant insights through which the challenges and opportunities of urban heritage conservation and urban prosperity can be analysed. Through mixed-method research—primarily relying on qualitative interviews with local stakeholders concerning the patterns of local conservation challenges and transformations in citizens’ livelihoods, quantitative data collection on tourist motivations and frequency, and a review of conservation policy—this article aims to determine not only how to balance commercialisation with conservation efforts but also how to cocreate social value with citizens to ensure both economic vitalities and to protect historical authenticity and integrity. The findings indicate that while commercialisation brings essential funds and revitalisation to the area, overcommercialisation raises the risk of gentrification and threatens historical authenticity. This research identifies practices that strike a balance between fostering an economically vibrant district and ensuring that heritage conservation remains at the forefront of development efforts. These findings can act as a blueprint for comparable heritage locations both in China and worldwide.